Multimedia Development Based on The Assemblr EDU Application in Human Reproductive System Material for Grade XI High School Students - Devita Sulistiana; Marinda Sari Sofiyana; Elsha Dewi Anggraini (Bioedukasi: Jurnal Pendidikan Biologi, 2026)
Based on an analysis of potential and problems involving 90 students in class XII in 3 top high schools in Blitar city/regency in 2023, the specific learning styles were 31,1% kinesthetic, 7,8% auditory, and 58,9% audiovisual. Data states that 64.4% of students find the material on the human reproductive system difficult to understand. Based on interviews with 3 biology teachers, it was revealed that preparing differentiated learning media is time-consuming. Teachers still predominantly use PPT-based media. The design of the multimedia, based on the Assemblr EDU application, is informed by data indicating that 93.3% of students favor multimedia-based learning. The objective of this Research and Development (R&D) is to develop and assess the feasibility of a multimedia platform based on the Assemblr EDU application as a teaching medium for material on the human reproductive system for grade XI high school students. This study research utilizes the R&D method, the research design following Sugiyono’s development model, limited to 7 stages with a quantitative descriptive approach. The feasibility test, validated by material, language, and media experts, yielded scores of 92.5%, 90.6%, and 89.23%, respectively, all falling within the “Very Feasible” criteria.  Additionally, the feasibility test, conducted through limited trials with teachers and students, yielded scores of 87.3% and 93.2% under the “Very Feasible” criterion. Thus, the developed Assemblr EDU application-based multimedia material on the human reproductive system for grade XI High School Students is considered suitable for learning activities